Digital Transformation Strategy to Increase the Competitive Advantage of the Hospitality Industry in Serang District, Banten - Rina Fitriana; Uud Wahyudin (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the digital transformation design strategy in creating competitive advantage in the hotel industry in Serang Regency, Banten Province. The method used is a descriptive qualitative approach, with data collection techniques through in-depth interviews, observations, and documentation studies of six hotels operating in the research area. The results of the study indicate that the implementation of digital transformation in Serang Regency is still limited to the use of online reservation platforms and social media for promotion, while the integration of advanced technologies such as the Internet of Things (IoT), self-check-in systems, and application-based services is still minimal. SWOT analysis identifies strengths in the form of digital platform adoption and active promotion, as well as opportunities through government support for the tourism sector. However, the low digital competence of the workforce and limited technology investment are the main weaknesses. The digital transformation strategy that was developed includes digitalization of core services, improvement of technology infrastructure, human resource training, and optimization of digital marketing. These findings emphasize that the success of digital transformation in the hotel industry requires integration between technology, organizational culture, and visionary digital leadership. The implications of this study provide theoretical contributions to the digital transformation model in the tourism sector as well as practical recommendations for industry players and policy makers to accelerate the digitalization of local tourism.